Preservice Teachers’ Readiness in Implementing Differentiated Science Learning of Independent Curriculum - Ainie, Irna Nurul; Yuniarti, Yeni; Sukardi, Rendi Restiana (Universitas Sebelas Maret, 2023)
This research is motivated by integrating natural and social sciences into science lessons of independent curriculum. This change significantly impacts the preservice teachers’ readiness in elementary school to implement science learning through an independent curriculum. This research investigates the preservice teachers’ readiness to teach natural sciences in an independent curriculum. This descriptive study involves eight elementary school preservice teachers from one of the LPTK in Bandung. The eight preservice teachers were selected based on purposive sampling. The instrument used in this study was a validated self-efficacy questionnaire. The data obtained were analyzed using descriptive statistics. The findings from this study indicate that preservice elementary school teachers are not fully prepared to be able to implement differentiated science learning. The results of the further investigation showed that this was due to the incomplete understanding of preservice elementary school teachers regarding pedagogical aspects, one of which was curriculum changes. The perceptions of preservice elementary school teachers about the diversity of student characteristics are also not by the principles of differentiated learning. This study concludes that preservice elementary school teachers need further information regarding the idea of an independent curriculum in differentiated science learning and guidance in preparing and implementing the lesson. Comprehensive understanding and differentiated science learning practices of independent curriculum need to be provided to preservice elementary school teachers. Therefore, this content needs to be taught to preservice elementary school teachers at LPTK.